Lysine-Dendrimer, a New Non-Aggressive Solution to Rebalance the Microbiota of Acne-Prone Skin - Julie Leignadier; Marie Drago; Olivier Lesouhaitier; Magalie Barreau; Albert Dashi; Oliver Worsley; Joan Attia-Vigneau (MDPI AG, 2023)
Acne is a chronic inflammatory skin disease that affects the quality of life of patients. Several treatments exist for acne, but their effectiveness tends to decrease over time due to increasing resistance to treatment and associated side effects. To circumvent these issues, a new approach has emerged that involves combating the pathogen Cutibacterium acnes while maintaining the homeostasis of the skin microbiome. Recently, it was shown that the use of a G2 lysine dendrigraft (G2 dendrimer) could specifically decrease the C. acnes phylotype (IAI) involved in acne, compared to non-acne-causing C. acnes (phylotype II) bacteria. In the present study, we demonstrate that the efficacy of this technology is related to its 3D structure, which, in contrast to the linear form, significantly decreases the inflammation factor (IL-8) linked to acne. In addition, our in-vitro data confirm the specific activity of the G2 dendrimer: after treatment of bacterial cultures and biofilms, the G2 dendrimer affected neither non-acneic C. acnes nor commensal bacteria of the skin (Staphylococcus epidermidis, S. hominis, and Corynebacterium minutissimum). In parallel, comparative in-vitro and in-vivo studies with traditional over-the-counter molecules showed G2's effects on the survival of commensal bacteria and the reduction of acne outbreaks. Finally, metagenomic analysis of the cutaneous microbiota of volunteers who applied a finished cosmetic product containing the G2 dendrimer confirmed the ability of G2 to rebalance cutaneous acne microbiota dysbiosis while maintaining commensal bacteria. These results confirm the value of using this G2 dendrimer to gently prevent the appearance of acne vulgaris while respecting the cutaneous microbiota.